Neuroprotection of luteolin against methylmercury-induced toxicityin lobster cockroach Nauphoeta cinerea (2016)
Luteolin (3_, 4_, 5, 7-tetrahydroxyflavone) is a polyphenolic compound found in foods of plant origin and has been reported to possess antioxidant and neuroprotective properties. However, there is dearth of information on the beneficial effects of luteolin on methylmercury (MeHg), a long-established neuro-toxic compound in animals and humans. This study evaluated the effect of luteolin on MeHg-inducedbehavioral and biochemical deficits, using lobster cockroach Nauphoeta cinerea as an alternative and complementary animal model. The insects were exposed for 35 consecutive days to either MeHg alone(0.05 mg/g feed) or in combination with luteolin at 0.25, 0.5 and 1.0 mg/g feed. Locomotor behavior was assessed using video-tracking software during a 10-min trial in a novel arena and subsequently, biochemical analyses were carried out using the cockroaches’ heads. Luteolin supplementation dose-dependentlyreversed the MeHg-induced locomotor deficits and enhanced the exploratory profiles of MeHg-exposedcockroaches as confirmed by track and occupancy plot analyses. Luteolin reversed the MeHg-inducedacetylcholinesterase activity inhibition, decreased dichlorofluorescein oxidation and lipid peroxidation levels, but increased total thiol level and catalase and glutathione S-transferase activities in the treated cockroaches. In conclusion, luteolin prevented oxidative stress indices and neurobehavioral deficits in a Nauphoeta cinerea model of MeHg toxicity.